Pelatihan Layanan Karir bagi Guru SMA di Kota Ambon - Prisca Diantra Sampe; Izak J Makulua; Hendra Suhry (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
The world of education and work is currently undergoing rapid change due to technological advances, globalization, and changing job market needs. Another emerging issue is students' low career readiness. Research shows that most high school students still fall into the moderate career readiness category, meaning they lack a well-developed career plan and are unable to make independent career decisions. This suggests that training can help guidance and counseling teachers adapt to the needs of modern, technology-based career services. Improved competency is also evident in the ability to develop career guidance and counseling programs and career counseling skills.